PEMANFAATAN PERALATAN PENGOLAHAN IKAN BERBENTUK MESIN UNTUK PENINGKATAN KAPASITAS PRODUKSI PADA KELOMPOK PENGOLAH DAN PEMASAR IKAN DI KAWASAN KONSERVASI PERAIRAN TWP GILI MATRA - Gigentika, Soraya; Hilyana, Sitti; Waspodo, Saptono; Paryono, Paryono; Sumsanto, Muhammad; Martanina, Martanina; Ashari, Rowi; Murdin, Lalu Ferdi Alfarisi; Amir, Sadikin; Nurliah, Nurliah; Damayanti, Ayu Adhita; Rahman, Ibadur; Larasati, Chandrika Eka; Himawan, Mahardika Rizqi; Jefri, Edwin; Lestariningsih, Wiwid Andriyani; Wahyudi, Rhojim; Sakina, Sholihati Lathifa (Jurnal Abdi Insani, 2024)
The fish processing and marketing group (poklahsar) in the Gili Matra Marine Protected Area has received intervention from the central government through Bappenas in the COREMAP-CTI III program. This intervention involves improving human resource capacity and providing grants for fish processing equipment. However, the limited duration of the program has resulted in suboptimal assistance in utilizing the donated fish processing equipment. Therefore, the involvement of universities in assisting the community is deemed necessary. This assistance activity aims to inform and educate the poklahsar about the use of fish processing equipment, particularly machines, to enhance production capacity in the Gili Matra Marine Protected Area. The assistance activities were carried out in July 2023 at the respective production locations of each poklahsar. The educational method for adults in this assistance activity involves lectures and hands-on practical training. The outcome of this assistance activity is an increased understanding and knowledge among poklahsar in the Gili Matra Marine Protected Area regarding the functions and uses of various machine-based fish processing equipment. Additionally, it was identified that some obstacles hinder optimizing machine-based equipment utilization, including a lack of understanding in using such equipment and limited market demand for processed fish products. In conclusion, the poklahsar have diverse views on using machine-based equipment, enabling them to optimize the use of such equipment despite the limited demand for processed fish products.